2022
DOI: 10.1007/s40477-022-00704-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of transcranial Doppler in assessment of cerebral blood flow in full term neonates with extreme unconjugated hyperbilirubinemia

Abstract: Purpose To evaluate the difference in cerebral blood flow in neonates with and without extreme unconjugated hyperbilirubinemia. Methods Transcranial Doppler parameters of 26 full term newborns with extreme unconjugated hyperbilirubinemia (UCH) were compared to 13 postnatal age and sex matched normal healthy neonates serving as controls. Resistance index (RI), pulsatility index (PI) and peak systolic velocity (PSV) were measured in the middle cerebral, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Studies have shown that IKAP health education model can improve patients' pregnancy outcomes and newborn health conditions. [28] In this study, patients with pregnancy-induced hypertension were chosen as the study objects to analyze the application effect of IKAP health education combined with cluster-based The For example, pregnancy index greatly outperformed the CG's, indicating that IKAP health education combined with cluster-based care had more obvious control effect. Prenatal anxiety levels showed statistically significant variations (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that IKAP health education model can improve patients' pregnancy outcomes and newborn health conditions. [28] In this study, patients with pregnancy-induced hypertension were chosen as the study objects to analyze the application effect of IKAP health education combined with cluster-based The For example, pregnancy index greatly outperformed the CG's, indicating that IKAP health education combined with cluster-based care had more obvious control effect. Prenatal anxiety levels showed statistically significant variations (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IKAP health education model can improve patients’ pregnancy outcomes and newborn health conditions. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%